2018
DOI: 10.1002/jper.17-0372
|View full text |Cite
|
Sign up to set email alerts
|

Association of marijuana use with oral HPV infection and periodontitis among Hispanic adults: Implications for oral cancer prevention

Abstract: Marijuana use was associated with periodontitis, but not with oral HPV infection. Further evaluation of the role of marijuana use in oral HPV infection and periodontitis may inform novel preventive public health strategies, as marijuana users could be at increased risk of oral cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
1
20
1
1
Order By: Relevance
“…All studies included in this systematic review, with the exception of López’ study, presents an elevated prevalence of periodontal disease associated with marijuana use was found. Data related to review question on overall sample in Lopez and Baelum study were not available, once the authors showed a stratified analysis by time of marijuana use and frequency of smoking.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…All studies included in this systematic review, with the exception of López’ study, presents an elevated prevalence of periodontal disease associated with marijuana use was found. Data related to review question on overall sample in Lopez and Baelum study were not available, once the authors showed a stratified analysis by time of marijuana use and frequency of smoking.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, 13 491 individuals were included, of which 49.5% were males. The studies were conducted in New Zealand, Chile, Australia, United States of America, and in the Puerto Rico . The design of most studies was cross‐sectional although one was prospective from a birth cohort .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations